Creative Hyper-Activation in Depression. Issue 4 (2nd October 2019) - Brenner, Leon S.
Abstract : A strong relationship between creativity and major depression has been attested to in many past studies. These suggest a correlation between high creative propensity and the prevalence of depression as well as attribute the implementation of creative tasks in therapy with the facilitation and reduction of depressive symptoms. This article supports the hypothesis of a bidirectional relationship between creativity and depression. Based on a theoretical framework proposed by Agamben in his critique of Freud, this article develops this hypothesis by associating depression with the non-adaptive application of a person's innate creativity. More specifically, it provides a model that associates the onset of depression with a unique form of non-adaptive hyper-activation of creative capacity. By distinguishing a unique mode of intransitive (object-less) creative hyper-activation in depression, it provides a wider explanatory scope for the vast array of studies attesting to a relationship between creativity and depression, and provides several prospects for the clinical facilitation of depression utilizing creative tasks.